Karton Ambalaj Üretimine Destek Sağlayan Elektronik Bilgi Ağının Taranması - ÖZDEMİR, LUTFİ; URAL, ELİF; ACAR BÜYÜKPEHLİVAN, GÜLHAN; ZELZELE, ÖMER BÜNYAMİN (My University, 2001)
Carton packagings are graplıical produets vvhich have important effects in inereasing sales and marketing vvith related to design quality and in improving company image, together vvith their carrying and proteeting duties. Hovvever, these are not short term designs like commercial or nevvspaper notices. Many produets keep their design of packagiııg vvithout changing for years. Tlıis is essential for many produets. This kind of produets vvith the design ehanges in packaging is not attraetive for the consumer or they produce conflicts in terms of their safety. Finally, the sales and marketing ehance gets dovvn and llıe company image is badly affeeted. In the present study; samples vvere selected from the most affeeted type of produets in these conditions and the differences betvveen the samples printed in the past and in llıe preseni vvere compared and the general ehanges establislıed. As a result, llıe polential causes and results of ehanges or deformations related to llıe time and the technique used vvere examined and the precautions to be laken vvere presenied.

Karton ambalajlar koruma ve taşıma işlevlerinden başka , tasarını kalitesine bağlı olarak satışın artmasında ve firma imajının güçlenmesinde etkili olan gratlk ürünleridir. Ancak bir afiş veya bir gazete ilanı gibi kısa süre içinde işlevi tamamlanan tasarımlar değildirler. Birçok iiriin ambalajı hiç değiştirilmeden yıllarca sunumda kalır ve böyle olması da zorunludur. Ambalajının tasarımında sıklıkla değişiklikler yapılan veya teknik nedenlerle bozulmalar oluşan bir ürün. alıcı tarafından benimsenmez veya güvenirlik açısından çelişkiler doğurur. Sonuçta satış şansı azalır, marka ve firma imajı da bundan zarar görür. Çalışmada, böyle durumlarda en çok etkilenebilecek olan ilaç ürün grubu içinden örnekler seçilerek ilk yıllardaki baskılarla yakın tarihteki basılmış örnekler incelendi ve genel değişiklikler saptandı. Sonu? olarak s-nmnnn ve teknik nedenlere bağlı değişim veya deformasyonlarııı olası nedenleri ve sonuçları irdelenerek alınabilecek önlemler tesbıt edildi.